The Effect of Signal Applications and Tax Literacy on Motor Vehicle Tax Payment Compliance with Tax Service Digitalization as a Moderator - Desiliany Desiliany; Novira Sartika (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the effect of the National Digital Samsat Application (SIGNAL) and tax literacy on Motor Vehicle Tax (PKB) payment compliance with tax service digitalization as a moderating variable. The study uses a quantitative approach with YSEM-PLSYanalysis through WarpPLS 7.0 and involves 228 SIGNAL user respondents in Bengkalis Regency. The results show that the SIGNAL application and tax literacy have a positive and significant effect on taxpayer compliance. However, the digitization of tax services is unable to moderate the relationship between the use of SIGNAL and tax literacy with tax compliance. These findings confirm that even though digital services are available, their effectiveness in strengthening compliance behavior is still limited, so it is necessary to improve the quality of the system and the utilization of digital services by the community.